DI BALIK CITRA IKLAN SHAMPOO PANTENE (Makna Bias Gender pada Iklan Pantene versi Labels Against Women di Televisi). - Rahmi Dyah Pratiwi; Handriyotopo Handriyotopo (TEXTURE : Art and Culture Journal, 2018)
ABSTRACTThis papaer is research on Pantene Shampoo advertisement Labels Against Women which visualizes gender bias and sexism. The aims are to find out messages, to outlines images conveyed through audio-visual advertising by comparing gender culture in Indonesia. Using qualitative descriptive research methods through Julia Kristevaâ€™s intertextual semiotic analysis. Analyze the frames of each scene to describe the ad as a whole, describing signs that contain elements of gender culture. As a result, this Pantene advertisement campaigned for gender equality, and determined working women as the targets. Keywords: advertisingPantene, gender, semiotics, and intertextuality.ABSTRAKPenelitian iklan Shampoo Pantene â€œLabels Against Womenâ€ memvisualkan bias gender dan seksisme untuk mengetahui pesan-pesan, menguraikan citra yang disampaikan melalui audio-visual iklan dengan mengkomparasikan sbudaya gender di Indonesia. Menggunakan metode penelitian deskriptif kualitatif melalui analisis semiotika intertekstualitas Julia Kristeva. Menganalisis frame tiap adegan untuk menggambarkan iklan secara keseluruhan, mendeskripsikan tanda yang mengandung unsur budaya gender. Hasilnya, iklan Pantene ini mengkampanyekan kesetaraan gender, dan menentukan wanita pekerja sebagai konsumen.Kata kunci: iklan Pantene, gender, semiotika, dan intertekstualitas.